Foreword. (2019) - Vergani, Laura; Guagliano, Mario
Abstract: The word "Bio" is used as prefix in many different scientific and industrial fields to define subjects and applications that have something to do with "life" or the living world. Nowadays a lot of different subjects are classified in the "bio" area: from materials inspired by biological microstructures for high-tech applications, to artificial bio-compatible tissues, from the imitation of efficient movements of some animal species to the design of surfaces for superior biocompatibility and many more could be cited. All these subjects originated different research fields with different aims and attracted the interest of many researchers acting in quite separate areas, with almost no relation